Manajemen Budaya Sekolah Dalam Meningkatkan Prestasi Belajar dan Karakter Sosial Siswa SD Negeri 10 Kabupaten Wonosobo - Nastiti, Feriska Desi (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine: (1) school culture activities at SD Negeri 10 Wonosobo; (2) student achievement; (3) student social character; and (4) the role of school culture in improving student learning achievement and social character. This study uses a qualitative descriptive method with observation, interview, and documentation techniques. Data analysis follows the Miles and Huberman model, through data reduction, presentation, and drawing conclusions and verification. The results of the study show: (1) School culture management is carried out through planning, organizing, directing, and evaluation as stated in the curriculum. Evaluation is carried out every month for continuous improvement. (2) Student learning achievement is very good, as evidenced by academic grades and various championships won. (3) Student social character is well developed, marked by an attitude of responsibility, self-confidence, discipline, politeness, and appreciation of achievement. (4) School culture contributes positively to improving student learning achievement and social character. Thus, a well-managed school culture can be an important factor in shaping character and improving student achievement at SD Negeri 10 Wonosobo.